Walking Towards Wellness: Exploring Community Views on Urban Walkability for a Healthier Lifestyle in Semarang - Kirana Prasetya Azizah; Bagus H. Setiadji; Haryono S. Huboyo (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Promoting active mobility, such as walking, is a key measure in creating a healthier urban environment. In support of Semarang City’s Urban Mobility Plan, which prioritises low-carbon strategies, the local government has undertaken extensive development of pedestrian infrastructure since 2017. This study investigates public willingness to utilise pedestrian pathways, a critical component in ensuring the effectiveness of such interventions. Data were collected through a survey involving 254 respondents across 24 major roads in Semarang. Findings indicate that walking is predominantly undertaken for shopping and health-related activities, typically covering distances between 200 and 800 metres on weekends. Destinations most frequented include shops, markets, stalls, and shopping centres. The results highlight the importance of integrating user-centred design into pedestrian infrastructure and emphasize the function of pedestrian paths as a social interaction space for both physical exercise and building community cohesion, thereby maintaining the mental health of residents.